Antioxidant and anti-ageing activities of cocoa bean extract for cosmeceutical use - Abdul Wahab, Norliza (2019)
Theobroma cacao which is best-known as ‘Food of the God’ by an ancient Greek, belongs to Sterculiaceae family. It is an indigenous plant from the tropical region of America which culture was further extended to equatorial areas of Africa and Asia. The goodness of T.cacao bean against cancer, cardiovascular-related diseases, certain neurodegenerative disorders and premature ageing have been often reported. However, information pertaining to antioxidant capacity and anti-ageing activity of potential Malaysian cocoa bean extract (CBE) for cosmeceutical use is limited. Therefore, the main objective was to determine the antioxidant capacity and anti-ageing activity of two types of cocoa beans’ clones, known as PBC140 and PBC123. Response surface methodology employing a central composite design throughout twenty experiments was conducted for the optimization of extraction condition, focusing on ethanol (30-80%, v/v), temperature (30-60oC) and extraction time (60-240 min). Optimal ethanol concentration (70% [v/v]) and extraction temperature (50oC) have resulted in the highest total phenolic (377 and 231 mg GAE/g DW, respectively) and total flavonoid content (73 and 63 mg RE/g DW, respectively). For antioxidant capacity, PBC140 was significantly higher (p>0.05) than PBC123 in term of 2,2-Diphenyl-1- picrylhydrazyl scavenging whereas ferric reducing antioxidant power and - carotene leanoleate bleaching assays showed no significant different (p>0.05). PBC140 was higher than PBC123 but with no significant different (p>0.05) in both anti-collagenase and anti-elastase when conducted on Ac-PLG-[2- mercapto-4-methyl-pentanoyl]-LG-OC2H5 and MeOSuc-Ala-Ala-Pro-Val-pNA substrates, respectively. PBC140 was cytotoxic at IC50=1100 μg/mL on 1x105 human dermal fibroblast (HDFa) cells/well at sixth passage or the highest average HDFa cell viability level. The extracted ribonucleic acid of HDFa treated with 1x103 μg/mL CBE significantly (p<0.05) downregulated the ultraviolet-induced matrix metalloproteinase-1 by 25-fold relative to calibrator. Ultraviolet A ratio for in vitro photoprotective effect of 0.1% (w/v) CBE formulation indicated 0.553 from the Boots Star Rating (Good). Intervention of approximately 500 mg 0.1% (w/v) CBE formulation on 20 human subjects aged between 30 to 46 years for 2 months duration in the in vivo skin efficacy studies recorded significant (p<0.05) percent changes of skin texture parameters, namely volume (-40%), energy (46%), contrast (-18%) and variance (-21%). The skin elasticity parameter for CBE formulation recorded significant (p<0.05) increment of ten times compared to placebo group. To conclude, Malaysian CBE is a potential active material due to the encouraging results of antioxidant capacity, in vitro anti-ageing, safety, and in vivo skin efficacy that meet the primary objective of producing harmless yet natural cosmeceutical with significant skin improvement.